A Study on the Psychological Structure and Mechanism of Shared Chinese Cultural Identity of University Students - Zhu, Dan; Lin, Xunyi (Frontiers in Psychology, 2022)
In previous studies, as an important object of inheritance and promotion of Chinese culture in Chinese colleges and universities, the psychological change mechanism of college students in the process of receiving cultural identity education has not attracted widespread attention. This study focuses on ideological and political education in colleges and universities, and innovatively believes that in order to improve college students' identification with Chinese culture, and make them consciously "internalize in mind and externalize in practice", it is necessary to explore their psychological structure and mechanism of action in the process of accepting identity education and take measures to actively intervene.The study employs the method of questionnaire investigation, acquiring 1119 effective samples from 30 universities in Fujian province. By establishing the theoretical framework of “cognitive identity - emotional identity - ideological identity - behavioral identity”, analyzing and examining the data, it’s found out that: (1) cognitive identity affecting behavioral identity positively in a noticeable way; (2) by raising individual emotional identity, cognitive identity strengthening university students’ behavioral identity; (3) cognitive identity inspiring behavioral identity with benefits of ideological identity; (4) it being verified that there exists an intermediary chain reaction between emotional identity, ideological identity and cognitive identity, behavioral identity. As a result, the followings are proposed: (1) further integrating the worthy Chinese traditional culture into university curriculum and developing students’ cognitive education of traditional culture; (2) exploring the aesthetic dimension of worthy Chinese traditional culture and deepening the students’ emotional identity of traditional culture; (3) demonstrating the essence of the worthy Chinese traditional culture and advancing the students’ ideological identity of traditional culture; (4) intensifying the practice of the worthy Chinese traditional culture and motivating the students’ behavioral identity of traditional culture.